Concept, Indications and Classification of Administrative Discretion - A. V. Girvits (Сибирское юридическое обозрение, 2014)
Nowadays discretion is the notion used loosely enough in the legal sphere. Consequently, in different situations connected with application of discretion it is interpreted in different ways. The article deals with the issues relating to the modern role of discretion in state administration, the notion of discretion and its distinctive features.